Implementasi PP No.90 Tahun 2010 Tentang Penyusunan Rencana Kerja Dan Anggaran Kementerian Negara/Lembaga Pada Direktorat Bandar Udara Direktorat Jenderal Perhubungan Udara - Siti Armala; Pandoyo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2020)
To realize good governance in relation to financial management, with the approval of the government House of Representatives has successfully established a package of legislation in the field of state finance, namely Law no. 17 of 2003 on State Finance, Law No. 1 of 2004 concerning the Treasury State, and Law No. 15 the Year 2004 on Management and Financial Responsibility State. The third law is the basis for the country's financial sector reform, from the planning, implementation, and accountability has a legal framework that ensures accountability and transparency of the state budget. Authors apply to research that is descriptive of the Directorate Airport describe in detail and specific to the data obtained in accordance with the facts, so that describe fundamental problems that are the focus of this paper. This study uses primary data sources and secondary data, then this type of research is a qualitative research approach. The study Budgeting Task Force has implemented a Performance-Based Budgeting which includes Performance Plan, Process, Determination of Performance Indicators, Output Indicators, and Outcome Indicators. Task Force Action Plan has been established consisting of 6 (six) activity has been fully implemented Performance-Based Budgeting consistently and can be used as guidelines for the implementation and monitoring and performance assessment